Correlation Of Clinical Severity And Extent Of Disease With Colonic Malignancy Trends Over Time In Ulcerative Colitis: A Study From North Karnataka - Batra, Nikhil; Hajare, Santosh (Journal of Neonatal Surgery, 2025)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease associated with variable clinical severity and an increased long-term risk of colorectal cancer (CRC), particularly in patients with extensive colonic involvement and persistent endoscopic inflammation. Indian data on long-term outcomes, especially malignancy risk, remain limited. Aim: To evaluate the correlation between disease extent, Mayo endoscopic severity, and the development of colonic malignancy in a cohort of UC patients from North Karnataka. Methods: A retrospective analysis was conducted on 122 UC patients over a 15-year period. Demographic characteristics, disease extent, clinical Mayo score, Mayo Endoscopic Score (MES), and CRC occurrence were recorded. UC diagnosis was confirmed by colonoscopy, contrast-enhanced CT (CECT), and histopathological examination. CRC diagnosis was similarly established through colonoscopy, imaging, and tissue biopsy. Results: The cohort included 77 males (63.1%) and 45 females (36.9%), with a mean age at diagnosis of 47 ± 11 years. Pancolitis was the most prevalent disease pattern (67.2%), followed by proctosigmoiditis (16.4%). Most patients presented with moderate-to-severe disease activity, with 54.1% having Mayo 3 scores and 49.2% having MES 3. Over the study period, 9 patients (7.4%) developed CRC 6 males and 3 females all of whom had long-standing pancolitis and severe endoscopic inflammation (MES 3). Conclusion: This North Karnataka cohort demonstrated a predominance of extensive and severe UC. Colonic malignancy occurred exclusively in patients with long-standing pancolitis and high inflammatory burden. These findings highlight the importance of early inflammation control and long-term surveillance in high-risk UC populations.